PERLINDUNGAN HUKUM PENGADAAN TANAH TERHADAP PERBUATAN MELAWAN HUKUM BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 3583 K/PDT/2018 - Telly Widjaya; Fransiscus Xavierius Arsin (The Juris, 2022)
Business activities which are State Strategic Projects or as National Vital Objects are often related to land acquisition for development in the public interest. Land acquisition must of course prioritize the principles of applicable laws and regulations. However, in practice there are often disputes in land acquisition and compensation that have been carried out by other parties. Research using normative juridical methods, this paper intends to provide an overview of legal certainty for right of way to the gas pipeline located along the Bontang forest area to Tanjung Santan, East Kalimantan, which is a National Vital Object and has been operating since 1975 and has received a permit from Governor of East Kalimantan Province. The land has previously also gone through a compensation mechanism which was carried out on a land use permit, at the request of the Agrarian Directorate of East Kalimantan Province to compensate for the loss of timber stands and objects on it to the holders of HPH (Forest Management Rights) but in practice, land disputes still arise. With Government Regulation Number 24 of 1997 concerning Land Registration, it should be a solution to provide legal certainty to owners of right of way to gas pipelines to deal with land disputes from other parties.